The collected writings of John Maynard Keynes, Volume 2, The economic consequences of the peace - Keynes, John Maynard 1883-1946 (The collected writings of John Maynard Keynes, 2013)
The Economic Consequences of the Peace was written by Maynard Keynes in 1919 following his resignation as Treasury representative at the Peace Conference at Versailles. It was this work that first made Maynard Keynes's name a household word, a figure of hatred and public criticism to some, a rallying point for rational thought and action to others. Written in the white heat of anger and despair, it vividly conveys to later generations Keynes's horror that clear thinking, human compassion and solemn pledges had been, in his eyes, destroyed by political opportunism